STRATEGI KOMUNIKASI HUMAS SMESCO INDONESIA DALAM PUBLIKASI PROGRAM UMKM MELALUI MEDIA SOSIAL INSTAGRAM - Keyjia, Nur Al; Sidharta, Veranus; Tambunan, Resman Muharul (Global Komunika : Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
Micro, Small and Medium Enterprises (MSMEs) not only create jobs, but also contribute to the country's economic growth and contribute to achieving the 17 sustainable development goals listed in the SDGs. Therefore, the use of communication strategies in publicizing MSME products is very crucial so that the message conveyed can run effectively. One of the effective communication tools in promoting MSMEs is social media, which can open up opportunities to increase sales of MSME products. This research will explore SMESCO Indonesia's public relations communication strategy in publishing MSME programs via Instagram social media. The method used in this research. The method used in this research is descriptive qualitative. The warrant for obtaining research data was given to the Head of Communication and Public Relations at Smesco Indonesia and the Communication and Public Relations Staff at Smesco Indonesia. The research results show that external and internal communication strategies as well as managing Instagram social media accounts in promoting MSME programs are effective tools in achieving organizational goals, namely supporting economic growth through promoting MSME products and building strong relationships with various interested parties.